Poesie und Trivialität in Risto Savins deutschen Liedtexten - Zimmermann, Peter (Muzikološki zbornik, 2012)
Most of the fifteen Lieder by Risto Savin which survive in his legacy are based on German poetry, while three of them are based on translations of foreign poetry into German. The article leaves it to the reader to decide whether the composer had a lucky hand in the choice of poems. Their authors are presented with a short biography and a discussion of their artistic output, as some of them are not well known today. On the basis of the first-publication dates of the poems, the article corrects some wrong composition dates given by Dragotin Cvetko. A supplement gives exact transcriptions of Savin's manuscripts of these Lieder, which are written in Deutsche Schreibschrift, the old German handwriting.
Keywords: nemška poezija; samospevi na nemška besedila; Savin, Risto; slovenski skladatelji; Širca, Friderik; vokalna glasba